HARMONIZATION OF REGIONAL ADMINISTRATION MANAGEMENT STYLE - I. Drogobitsky (Управленческие науки, 2016)
In the search for ways to further improve the effectiveness and efficiency of organizational management modern economic science is increasingly drawn to the psychological and sociological methods of integrating them into the overall management methodology. One of the most significant results of this integration is the concept of “management style”, which is absolutely clearly perceived at the level of the qualitative characteristics of organizational management, by causing different interpretations at the level of its quantitative measurement. This paper presents an approach to the measurement of leadership style, which is based on the theory of change management in the interpretation of Isaac Adizes. The key point of this theory is that the successful management of any economic system, its management must cope with four kinds of administrative activity: execution of (P),administration (A), entrepreneurship (E) and integration (I). If the management team no people capable of providing at least one type of control, the organization has managed to deal with unbalanced control, which cannot ensure its normal functioning.Based on this postulate the metric notion of «management style» and the rules for determining its value are discussed in the article. The applicability of this approach and the potential benefits of its use is demonstrated by measuring the leadership styles of key job positions hypothetical regional administrations to develop proposals for its improvement.